Contributions and Contributions of Technological Mediations in Achieving Significant Improvements in the Teaching-Learning Process. A Systematic Review - Navarro, Rafael Cecilio (Journal of Ecohumanism, 2024)
The objective of this research was to carry out a systematic review of the contribution of technological mediations in the teaching-learning process in Latin America. Regarding the methods used, the PRISMA methodology was used for systematic review work. Through the search carried out in Google Scholar, and the Dialnet and Scielo databases, and the application of the steps established by the PRISMA methodology, the final amount equivalent to 25 selected scientific articles was obtained. Indeed, the highest proportion of scientific articles (24%) has corresponded to the years 2021, 2022 and 2023 with 6 articles selected for each case, followed by the statistical figures for the years 2020 (20%) and 2019 (8%) with 5 and 2 articles selected, respectively. On the other hand, it was possible to determine that the highest proportion of selected scientific articles (36%) has corresponded to the country of Colombia with the figure of 9 studies; followed by the countries of Ecuador (20%), Mexico (16%), Costa Rica (12%) and Argentina (8%). It was concluded that, in the 25 selected articles, positive effects or implications of technological mediation on the teaching-learning process have been reported, mainly in the subjects of Reading, Mathematics, Chemistry and Physics. The positive effects of technological mediation have materialized in the improvement of the teaching-learning process, the increase in academic performance, the development of skills, a more active role of the student population, and greater motivation and attention in students.